Determining the impacts of climate change on Spatio-temporal patterns of meteorological drought using SPI: A case study of Ain Defla, Algeria. - Attou, Alaa Eddine; Azouzi, Blel; Bouacha, Mohamed Islem (Journal of Environmental Geography, 2023)
As an associated aspect of climate change, drought has become a severe challenge in different parts of the world, especially in regions where life depends on predominantly rain-fed agriculture. The Ain Defla study area is mostly agricultural land, most of its activity depends on rain. In recent years, droughts of varying impact and severity have affected crops. Therefore, this study aimed to identify and study the regions that are most vulnerable to drought in terms of time and space. Moreover, it provides a detailed picture of the drought in the region and finds appropriate solutions in the event of its return in the future. The Standardized Precipitation Index (SPI) and the deviation from the average (EM) were calculated annually for 38 years for 13 stations from 1981 to 2019 within the study area. GIS was used to compile digital maps to visualize the spatial distribution of rainfall (P) and the difference in rainfall (EM) and determine the aridity using SPI values within the region based on the statistical method of Kriging. The Ain Defla region was subjected to drought of varying intensity and impact during the years (1983, 1989 and 2000), which extends with a decreasing value from east to west. Some wet years were also observed (2013 and 2018). Most years were in the moderate category by 60%. It is possible to rely on rain-fed agriculture in the western regions, that were less prone to drought during the study period compared to the eastern part, an area where drought is stable on an ongoing basis.